Evaluation of the Urine POC-CCA Test Accuracy in the Detection of Schistosoma mansoni Infection: A Systematic Review and Meta-Analysis - Getaneh Alemu; Endalkachew Nibret (Journal of Tropical Medicine)
Background. Schistosomiasis is a common public health problem throughout the world and Schistosoma mansoni is the most prevalent species in Africa. Most endemic countries use the Kato–Katz (KK) stool smear examination for diagnosis, mapping, and monitoring of intervention programs. However, its poor sensitivity calls for an urgency to evaluate and use more accurate diagnostic tools, of which detection of circulating cathodic antigen (CCA) in urine seems promising. Methods. Studies published until May 2022 were searched from PubMed, Google Scholar, and grey literature for systematic review and meta-analysis following the PRISMA guideline. Eligible studies were selected based on preset inclusion and exclusion criteria. Quality of included studies was assessed using the QUADAS-2 tool. Heterogeneity between studies was assessed using Cochrane Q test and I2 test statistics. Data were analyzed using Review Manager 5.4.1 and Meta-DiSc 1.4 software programs. Results. Thirty-seven studies published in 29 papers and enrolling 21159 study participants were included for analysis. Overall analysis of Point-of-Care Circulating Cathodic Antigen (POC-CCA) test against KK reference standard revealed a pooled sensitivity and specificity of 0.86 (95% CI: 0.85–0.87) and 0.66 (95% CI: 0.65–0.67), respectively. Subgroup analysis among 24 studies comparing single POC-CCA with test single KK revealed a high sensitivity (0.88) but low specificity (0.66). Based on findings of 24 studies, the area under the curve (AUC) for the systematic receiver operating characteristic (SROC) curve was 0.7805, indicating that the POC-CCA test effectively separates those with the disease from those who do not have it. Higher sensitivity estimates of 0.93 and 0.90 were reported when comparisons were made between test results of 2 urine and 1 stool samples, and 3 urine and 3 stool samples, respectively. Single POC-CCA test resulted in a pooled sensitivity estimate of 0.81 (95% CI: 0.78–0.84) as evaluated by the polymerase chain reaction (PCR) reference test. Conclusions. The POC-CCA test has higher sensitivity than KK and may serve as a routine diagnostic alternative for disease diagnosis, mapping, and monitoring of interventions. However, its accuracy should further be evaluated at different transmission settings and infection intensity.